2009
DOI: 10.1111/j.1600-065x.2009.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic view on domains mediating STIM1–Orai coupling

Abstract: Calcium (Ca2+) entry into non-excitable cells is mainly carried by store-operated channels, which serve essential functions ranging from regulation of transcription to cell growth. The best-characterized store-operated current, initially discovered in T lymphocytes and mast cells, is the Ca2+ release-activated Ca2+ (CRAC) current. The search for the molecular components of the CRAC channel has recently identified stromal interaction molecule 1 (STIM1) as the Ca2+ sensor in the endoplasmic reticulum (ER) and Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 96 publications
2
80
0
Order By: Relevance
“…Previous studies on the mechanics of SOCE have established that colocalization of STIM1 puncta with Orai CRAC channels equates with activation of calcium entry (12,13,26,(30)(31)(32)(33). Furthermore, while there are CRAC channels other than Orai1 to Orai3, such as select members of the TRPC family, activation of TRPC channels first requires colocalization of STIM1 and an Orai channel before the TRPC channel can be recruited and activated (16,17).…”
Section: Yfp-stim1 Biosensor Cell Linementioning
confidence: 99%
“…Previous studies on the mechanics of SOCE have established that colocalization of STIM1 puncta with Orai CRAC channels equates with activation of calcium entry (12,13,26,(30)(31)(32)(33). Furthermore, while there are CRAC channels other than Orai1 to Orai3, such as select members of the TRPC family, activation of TRPC channels first requires colocalization of STIM1 and an Orai channel before the TRPC channel can be recruited and activated (16,17).…”
Section: Yfp-stim1 Biosensor Cell Linementioning
confidence: 99%
“…Human STIM1 has 685 amino acids and consists of an approximately 22 kDa N-terminal portion (STIM1-N) located in the ER lumen, a single transmembrane segment and an approximately 51 kDa C-terminal portion (STIM1-C) in the cytoplasm (2). The STIM1-N can be further divided into tandem EF-hand and sterile alpha motif domains (16), whereas the STIM1-C encompasses two coiled-coil domains, a Pro/Ser-rich domain and a Lys-rich domain (17). Structural investigation and biochemical evidence revealed that STIM1-N alone was capable of promoting the transition of itself from a monomer to an oligomer upon release of Ca 2þ from the first EF-hand of STIM1-N; this release is thought to be an initiation event for capacitive Ca 2þ entry (16,18).…”
mentioning
confidence: 99%
“…Additionally, recent mutagenesis studies have implicated conserved acidic residues, including E106 and E190 in the first and third predicted transmembrane (TM) segments, and D110, D112, and D114 in the TM1-TM2 linker region of human Orai1 in shaping ion selectivity (7-10). These studies have led to the notion that the TM1 and TM3 segments of Orai1 flank the ion conduction pathway of the CRAC channel with the acidic residues within these segments forming coordinating sites for the conducting ions (9,11).…”
mentioning
confidence: 99%